2012
DOI: 10.1016/j.joca.2012.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PTH [1-34] on synoviopathy in an experimental model of osteoarthritis preceded by osteoporosis

Abstract: In our model of OA aggravated by previous OP, synoviopathy correlated well with cartilage damage. Intermittent PTH [1-34] administration ameliorated both hyperplasia and fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…Bellido et al 123 demonstrated that the improvements in the microstructure and integrity of subchondral bone due to PTH may prevent cartilage damage progression in rabbits with early OA preceded by osteoporosis, underlining the intimate crosstalk between articular cartilage and subchondral bone. Intermittent PTH administration also ameliorated synovial changes associated with cartilage damage 124 . Although further research is warranted, studies of bone-forming agents can provide novel targets in subchondral bone remodelling for the treatment of OA.…”
Section: Bone-forming Agents: Parathyroid Hormone (Pth)mentioning
confidence: 89%
“…Bellido et al 123 demonstrated that the improvements in the microstructure and integrity of subchondral bone due to PTH may prevent cartilage damage progression in rabbits with early OA preceded by osteoporosis, underlining the intimate crosstalk between articular cartilage and subchondral bone. Intermittent PTH administration also ameliorated synovial changes associated with cartilage damage 124 . Although further research is warranted, studies of bone-forming agents can provide novel targets in subchondral bone remodelling for the treatment of OA.…”
Section: Bone-forming Agents: Parathyroid Hormone (Pth)mentioning
confidence: 89%
“…In vitro studies have indicated that the beneficial effects of PTH(1-34) on chondrocytes involve binding to parathyroid hormone/parathyroid hormone-related peptide receptor (PTH1R) through activated multiple pathways 6e8 . In addition to the direct effects on chondrocytes, there has been a study in an OA model indicating that PTH may also reduce synoviopathy 9 . There have also been studies showing that the improvement of subchondral bone integrity in response to PTH contributes to the reduction of cartilage damage progression in animal models 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Although obvious differences exist between idiopathic OA in humans and our rabbit mechanical model of OA preceded by OP, the microstructure impairment at subchondral bone associated with an increased remodeling has been shown to aggravate cartilage damage [13]. In further studies carried out in the same animal model, we demonstrated that the improvement of microstructural and remodeling parameters at the subchondral bone reduces the progression of cartilage damage [14], and those structural parameters were also well correlated with synoviopathy score [15]. Thus, subchondral bone abnormalities, particularly increased remodeling, play a crucial role in joint damage during the development and progression of OA.…”
Section: Introductionmentioning
confidence: 62%
“…In contrast, thickening of the subchondral plate occurs in animal models of surgically induced OA corresponding to late-stage disease [5,73]. Interestingly, the improvement of subchondral bone integrity by PTH use reduced the progression of cartilage damage and synoviopathy in experimental OA preceded by OP [14,15]. Therefore, low bone mass or established OP may be a deleterious factor for joint cartilage integrity in a subgroup of individuals who would belong to a specific clinical setting in OA initiation, healthy cartilage, and established OP, among four possible subsets originated from the interplay between articular cartilage integrity and subchondral bone mineralization throughout the OA process [7].…”
Section: Discussionmentioning
confidence: 99%